Diabetes mellitus: alterações metabólicas e mitocondriais em células epiteliais corneanas - Mussi, Natalia [UNIFESP] (2022)
Purpose: Diabetic Keratopathy affects approximately 70% of diabetic patients. Mitochondrial dysfunction is considered a central feature underlying diabetic complications. The purpose of this study was characterized mitochondrial alterations in telomerase-immortalized human corneal epithelial (hTCEpi) cells exposed to hyperglycemic and hyperosmotic stress, also the changes in primary cultured diabetic human corneal epithelial cells (HCECs). Methods: To determine the effects of diabetes on mitochondria and metabolism, donor human corneas from diabetics were obtained from Tissue Transplant Services at UT Southwestern Medical Center. Primary cultures were generated using an established lab protocol. HCECs and hTCEpi cells were cultured in a defined serum-free keratinocyte growth media containing 6 mM of glucose. Cells were cultured for 24h, 3, 5, 7, 9 or 14 days in media with additional 19mM of glucose. Cells supplemented with 19 mM mannitol were used as an osmotic control. Mitochondrial morphology and polarization were assessed using MitoTracker Green, TMRE, and JC-1. Metabolic changes were quantified in real time using a Seahorse metabolic flux analyzer. Cell cycle were determined by staining with Propidium Iodide and analyzed using the Celigo imaging cytometer. Cell migration was evaluated by the wound healing assay and the cells proliferation was characterized by daily cell count for 7 or 14 days. Results: The HCECs cells from diabetic patients showed alterations in mitochondrial polarization and severe fragmentation. The hTCEpi cells exposed to acute hyperglycemia showed no abnormalities in cell cycle control and metabolism. Chronic exposure of hTCEpi cells to hyperglycemia (14 days) triggered cell cycle arrest in G0/G1 phase. At 14 days there was also a decrease in cell migration in the groups exposed to hyperglycemic and hyperosmotic stress. However, cell proliferation remained unchanged after both 7 and 14 days. Using JC-1, cells cultured in high glucose for 14 days showed a loss of polarization and mitochondrial fragmentation but this wasn’t significant in comparison to hyperosmolar stress. Metabolic activity was unchanged in cells cultured in high glucose for 24 hours. By day 3, cells showed a measurable drop in spare respiratory capacity that remained decreased through day 14. By day 5, glycolysis (ECAR) began to decrease and remained low through day 9. At days 7 and 9, OCR was increased, shifting cells towards a more respiratory phenotype. By day 14 OCR decreased and ECAR increased to normoglycemic levels and the phenotype became glycolytic again. There was also a sharp drop in others mitochondrial metabolic parameters. Discussion: Chronic, not acute, exposure to high glucose negatively impacts mitochondrial structure and function. The decline in mitochondrial activity was associated with a recovery of glycolysis, indicative of metabolic adaptation.